2020
DOI: 10.15446/agron.colomb.v38n2.82644
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional characterization of Moringa oleifera leaves, seeds, husks and flowers from two regions of Mexico

Abstract: Moringa oleifera (MO) is a native tree species found in the south of the Himalayas, India, Bangladesh, Afghanistan and Pakistan that is used commercially to produce tea, animal fodder and herbal medicines. The aim of the present study was to determine the nutritional characteristics of different parts of the MO plant from two regions of Mexico (States of Guerrero and Sonora). The proximal composition analyses (protein, lipids, ashes and fiber) were carried out according to the methods of the Association of Off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…The results indicated that Moringa oleifera flower powder is a good source of fibre, proteins and carbohydrates. These results were compared with the results reported by Guzmán-Maldonado et al (2020), in which the protein content of Moringa oleifera flowers was 14.94%, the ash content was 8.86% and the carbohydrate content was 57.88%. Proximate analysis of Moringa oleifera flower powder done by Arise et al (2014) showed significant differences in protein, fat, fibre, ash and carbohydrate contents of the flower powder such as protein (25.16%), fat (1.57%), fibre (7.55%), ash (6.01%) and carbohydrates (53.67%).…”
Section: Proximate Analysismentioning
confidence: 65%
See 2 more Smart Citations
“…The results indicated that Moringa oleifera flower powder is a good source of fibre, proteins and carbohydrates. These results were compared with the results reported by Guzmán-Maldonado et al (2020), in which the protein content of Moringa oleifera flowers was 14.94%, the ash content was 8.86% and the carbohydrate content was 57.88%. Proximate analysis of Moringa oleifera flower powder done by Arise et al (2014) showed significant differences in protein, fat, fibre, ash and carbohydrate contents of the flower powder such as protein (25.16%), fat (1.57%), fibre (7.55%), ash (6.01%) and carbohydrates (53.67%).…”
Section: Proximate Analysismentioning
confidence: 65%
“…These results were compared with the results reported by Guzmán‐Maldonado et al . (2020), in which the protein content of Moringa oleifera flowers was 14.94%, the ash content was 8.86% and the carbohydrate content was 57.88%. Proximate analysis of Moringa oleifera flower powder done by Arise et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These values are even higher than the ones observed in leaves, which are currently the most commercialized part of the plant. 23 Leaves contained more than two times as much protein (29-36%) compared to pods (11-15%). Similarly, nutrients including calcium and iron are significantly higher in leaves (2314-3487 ppm and 276-418 ppm, respectively) than in pods (2017-2032 ppm and 61-68 ppm, respectively).…”
Section: Nutritional Valuesmentioning
confidence: 96%
“…The findings of 19 showed that the leaves of Chenopodium quinoa had more important protein than the grains, as well as inorganic nutrients. Corroborating observations were addressed by 21 in the leaves, flowers, and seeds of Moringa oleifera.…”
mentioning
confidence: 99%